Antiproliferative terpenoids and alkaloids from the roots of Maytenus vitis-idaea and Maytenus spinosa - Rojo de Almeida, Maria Tereza (2010)
Investigation of the organic extracts of the roots of Maytenus vitis-idaea and Maytenus spinosa, collected in the province of Salta, Argentina, led to isolation of eighteen compounds belonging to several classes. From M. vitis-idaea, eight methylenequinone celastroids (1-8) were isolated, four of which (4-7) were hitherto unknown. Additionally, from M. spinosa, two known celastroids, a known celastroid dimer (9), three pentacyclic triterpenoids (10-12) and six β-dihydroagarofuran sesquiterpenoid alkaloids (13-18) were identified. Compounds 4-7 were active against six solid tumor cell lines at micromolar concentrations.